THE ROLE OF DIGITAL LITERACY OF PRE-SERVICE AND IN-SERVICE EFL INSTRUCTORS IN POST PANDEMIC COVID-19 - H. Kubra Er (Інформаційні технології і засоби навчання)
There is a need to pay more attention to the incorporation of digital technologies in teaching English as a Foreign Language (EFL) due to the increased importance of digital technology and digital literacy highlighted by the COVID-19 pandemic. The digital proficiency of teachers is crucial for effective teaching and learning in the 21st century, especially in the context of foreign language education [1]. In this context, this study investigates the role of digital literacy of pre-service and in-service EFL instructors post-pandemic. Participants are N:165 EFL pre-service and in-service instructors. The current study has a quantitative design, the data tool is the Digital Literacy Questionnaire for Language Teachers. The data is analyzed via the Mann-Whitney U test, Wilcoxon Signed Rank Test, descriptive analysis for one of the questionnaire items and content documentation for the last open-ended question for of the questionnaire. The findings of the study indicate that there are significant differences between Pre-service and In-service EFL Instructors for some of the items. Besides, as the findings suggest lack of skills and knowledge of teachers, lack of training, lack of budget, and lack of interest of teachers are among the factors affecting the use of digital technologies for foreign language teaching. The findings undeniably confirm the vital importance of digital literacy in teaching English as a Foreign Language (EFL) in the digital age, highlighting the need for teachers to actively acquire and employ it. Therefore, it is essential for EFL teachers to include digital literacy in their teaching methods by making use of a range of digital technologies, including Web 2 tools that provide several capabilities. The results also indicate the necessity of teacher training programs focused on enhancing the digital literacy skills of English as a Foreign Language (EFL) instructors.